Petri Nets in Science and Engineering - Campos-Rodriguez, Raul; Alcaraz-Mejia, Mildreth (IntechOpen, 2018)
This book presents a collection of chapters from different areas of science and engineering, where Petri Nets have been shown to be a useful tool for the design and modeling of the problems that arise in such fields. The areas covered in this book include manufacturing systems, authentication and cyber-security, computer architectures, mechanical systems, process mining, control theory and time analysis. The main focus of the chapters was to be illustrative, to help the development of intuitive ideas that may guide the reader to adopt Petri Nets in their scientific or engineering work. However, there are other chapters with deep mathematical basis such as time analysis. Whenever possible, models, graphics and examples illustrate the developed concepts.